STUDI BANDING PENGGUNAAN GIS DALAM PERENCANAAN WILAYAH DAN KOTA: ANTARA PENDEKATAN PARTISIPATIF DAN MANAJEMEN TEKNIS - Lumbangaol, Henry Paulus; Lubis, Ruri Prihatini; Hidayat, Wahyu (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Geographic Information Systems (GIS) have become essential tools in supporting regional and urban planning. This study compares two approaches to GIS utilization: technical-based village road management in Kapuas Hulu and the application of GIS for urban spatial planning. The first study employs Google Maps API to provide village road data, enhancing operational efficiency in the inventory and maintenance of local infrastructure. The second study leverages high-resolution spatial data from remote sensing to develop urban spatial plans that address disaster risk mitigation and infrastructure needs. The findings reveal that the technical approach is more cost-efficient and easier to implement at the local scale, while the strategic approach has broader impacts for long-term planning but requires significant investment. Differences in coverage, user involvement, and data complexity highlight the strengths and limitations of each approach. This study recommends integrating the two approaches to create a holistic GIS system. Technical GIS can support local data collection, while strategic GIS provides comprehensive analysis for large-scale decision-making. With this integration, regional and urban planning can become more efficient, inclusive, and sustainable